Perspectives of peaceful school on vocational school Students: A narrative research - Eko Susanto; Sunaryo Kartadinata; Ilfiandra Ilfiandra (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This paper aims to explore the school of peace in the perspective of students in vocational schools. School peace suspected as one of the factors that will determine the formation and behavior of student achievement in school. The narrative method chosen in this study whereas the focus of the study follows the excavation methods offered by Mishler. The study conducted showed that every student has no experience of peace in schools. However, students can receive no peace until he lost condition at meal time. The findings further that there are three things that make students not peaceful, the rules of the school, peer relationships, and the demands of parents and schools.